2021
DOI: 10.46743/2160-3715/2021.4874
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Experience of Anxiety Among Final Year Students at University: A Thematic Analysis

Abstract: The transition from undergraduate study to a postgraduate career can be an anxiety provoking experience for many students. In this study, we explore the shared experience of five “anxious” undergraduate students as they transition from higher education towards their postgraduate careers. Using a qualitative methodology, semi-structured interviews were conducted with five female undergraduate students from different courses at a UK university. A thematic analysis revealed two overarching themes: perceived press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…This finding is consistent with another study where international students who stayed in the UK and USA were more likely to experience higher levels of perceived stress, anxiety, and depression symptoms than returnees (Lai et al, 2020). Finally, compared to students who were not in the final year of undergraduate or postgraduate study, final-year students reported higher perceived stress amid the pandemic, like findings of Keane et al (2021) on the mental health of final-year nursing students where students found challenging to manage the transition to work or continuing education. Consequently, our study suggests that it is imperative to support international students' mental health, particularly for students who are staying in Canada and/or in their final year of study.…”
Section: Mental Health Assessmentssupporting
confidence: 90%
“…This finding is consistent with another study where international students who stayed in the UK and USA were more likely to experience higher levels of perceived stress, anxiety, and depression symptoms than returnees (Lai et al, 2020). Finally, compared to students who were not in the final year of undergraduate or postgraduate study, final-year students reported higher perceived stress amid the pandemic, like findings of Keane et al (2021) on the mental health of final-year nursing students where students found challenging to manage the transition to work or continuing education. Consequently, our study suggests that it is imperative to support international students' mental health, particularly for students who are staying in Canada and/or in their final year of study.…”
Section: Mental Health Assessmentssupporting
confidence: 90%
“…As most students were coming to the end of their time at college, the increase in mental health issues may reflect increased concern about pending assignments and upcoming exams [25]. Moreover, as the majority of this cohort were completing college, they may have been concerned about making the transition to the next stage in their lives following college [26] and their future prospects. Indeed, many students in this study reported that the pandemic had a very negative impact on their college experiences and plans for the future.…”
Section: Discussionmentioning
confidence: 99%